1997
DOI: 10.1073/pnas.94.11.5605
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 is a component of the RNA polymerase II holoenzyme

Abstract: The familial breast-ovarian tumor suppressor gene product BRCA1 was found to be a component of the RNA polymerase II holoenzyme by several criteria. BRCA1 was found to copurify with the holoenzyme over multiple chromatographic steps. Other tested transcription activators that could potentially contact the holoenzyme were not stably associated with the holoenzyme as determined by copurification. Antibody specific for the holoenzyme component hSRB7 specifically purifies BRCA1. Immunopurification of BRCA1 complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
347
0
5

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 422 publications
(363 citation statements)
references
References 32 publications
11
347
0
5
Order By: Relevance
“…The role of p53 as a transcription factor is well-established (Vogelstein and Kinzler, 1992) and appears to be important for its ability to arrest cell cycle progression as well as to induce apoptosis (Levine, 1997). BRCA1 has been postulated to function as a coactivator of transcription, based on its localization as a component of RNA polymerase II holoenzyme and transactivation function (Chapman and Verma, 1996;Monteiro et al, 1996;Somasundaram et al, 1997;Scully et al, 1997a). The observation that BRCA1 is a transcriptional coactivator of p53, including strong upregulation of expression of the bax gene, provides a novel mechanism for apoptosis induction and tumor suppression by BRCA1.…”
Section: Brca1 Regulates Of P53 Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of p53 as a transcription factor is well-established (Vogelstein and Kinzler, 1992) and appears to be important for its ability to arrest cell cycle progression as well as to induce apoptosis (Levine, 1997). BRCA1 has been postulated to function as a coactivator of transcription, based on its localization as a component of RNA polymerase II holoenzyme and transactivation function (Chapman and Verma, 1996;Monteiro et al, 1996;Somasundaram et al, 1997;Scully et al, 1997a). The observation that BRCA1 is a transcriptional coactivator of p53, including strong upregulation of expression of the bax gene, provides a novel mechanism for apoptosis induction and tumor suppression by BRCA1.…”
Section: Brca1 Regulates Of P53 Functionmentioning
confidence: 99%
“…Evidence implicates a role for BRCA1 in the control gene expression. BRCA1 contains a nuclear localization signal (Thakur et al, 1997), a C-terminal domain that transactivates gene expression when fused to a heterologous DNA binding domain (Chapman and Verma, 1996;Monteiro et al, 1996) and BRCA1 has been found as a component of RNA polymerase II (Scully et al, 1997a).…”
Section: Introductionmentioning
confidence: 99%
“…Deleterious mutations in BRCA1/BRCA2 were identified in 24% of our 256 high-risk French Canadian breast/ovarian cancer families, 4 supporting that a significant proportion of high-risk breast cancer families still remain unexplained by either germline mutations in high penetrance BRCA1/2 alleles or other lower penetrance genes. [5][6][7][8][9][10] Several structural motifs allow the BRCA1 protein to interact with cellular proteins to regulate diverse biological functions such as control of transcription 11 and DNA damage repair. 12 Therefore, BRCA1-interacting proteins implicated in these cellular pathways represent attractive candidates with regard to breast cancer susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…28 BAP1 was suggested to regulate the BRCA1/BRCA2-RAD51 DNA repair complex. 29 Given the known implication of BRCA1 in DNA repair 12 and its interaction with RNA pol II, 11 which is linked to transcription-coupled repair (TCR) processes, a role for BAP1 in TCR has been suggested. 30 It has been reported that mutation of an amino acid of BAP1 in its BRCA1-binding domain (L691P) abolishes the BAP1-BRCA1 interaction.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent ®ndings demonstrating an association between BRCA1 and Rad 51 proteins suggest a role for this protein in DNA repair (Scully et al, 1997a). However, the presence of a transactivation domain in BRCA1 and its stable association with RNA Polymerase II holenzyme (Scully et al, 1997b) indicate that BRCA1 might also be involved in the regulation of transcription. These two hypotheses, which are not mutually exclusive, stress that BRCA1 may have an important role in cellular di erentiation and proliferation.…”
Section: Introductionmentioning
confidence: 99%